Mergers of equals and unequals - Valerie Smeets; Kathryn Ierulli; Michael Gibbs (Institute for the Study of Labor (IZA), 2006)
We examine the dynamics of post-merger organizational integration. Our basic question is whether there is evidence of conflict between employees from the two merging firms. Such conflict can arise for several reasons, including firm-specific human capital, corporate culture, power, or favoritism. We examine this issue using a sample of Danish mergers. Controlling for other effects, employees from the acquirer fare better than employees from the acquired firm, suggesting that they have greater power in the newly merged hierarchy. As a separate effect, the more that either firm dominates the other in terms of number of employees, the better do its employees fare compared to employees from the other firm. This suggests that majority / minority status is also important to assimilation of workers, much as in ethnic conflicts. Finally, greater overlap of pre-merger operations decreases turnover. This finding is inconsistent with the view that workers of the two firms substitute for each other, creating efficiencies from merger. However, that result and our other findings are consistent with the view that more similar workers (in terms of either firm- or industry-specific human capital) are easier to integrate post merger.
urn:nbn:de:101:1-2009030919
Keywords: 330